The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1104/pp.81.3.792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl and CaCl2 on Ion Activities in Complex Nutrient Solutions and Root Growth of Cotton

Abstract: Sodium displaces Ca2 from membranes (GR Cramer, A Liiuchli, VS Polito Plant Physiol 1985 79: 207-211) and this can be related to the (Ca2`)/(Na')2 activity ratio in the external solution (GR Cramer, A Lauchli 1986 J Exp Bot 37: 321-330). Supplemental Ca2" is known to mitigate the adverse effects of salinity on plant growth. In this report we investigated the effects of NaCl (0-250 millimolar) and Ca2" (0.4 and 10 millimolar) on the ion activities in solution and on root growth of cotton (Gossypium hirsutum L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
4

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(93 citation statements)
references
References 13 publications
5
83
1
4
Order By: Relevance
“…1). This beneficial effect of calcium on the development of plants grown under saline conditions has been reported previously (Cramer et al, 1985(Cramer et al, , 1986(Cramer et al, , 1988). Short-term experiments performed by adding supplemental calcium to the saline growth media had only ameliorative effects under NaCl stress (Azaizeh & Steudle, 1991 ;Azaizeh et al, 1992).…”
Section: mentioning
confidence: 66%
See 2 more Smart Citations
“…1). This beneficial effect of calcium on the development of plants grown under saline conditions has been reported previously (Cramer et al, 1985(Cramer et al, , 1986(Cramer et al, , 1988). Short-term experiments performed by adding supplemental calcium to the saline growth media had only ameliorative effects under NaCl stress (Azaizeh & Steudle, 1991 ;Azaizeh et al, 1992).…”
Section: mentioning
confidence: 66%
“…Calcium ions are well known to have regulatory roles in metabolism, and sodium ions may compete with calcium ions for membrane-binding sites. It has been hypothesized that high calcium levels can protect the cell membrane from the adverse effects of salinity (Cramer et al, 1986). Also, calcium and apoplastic water potential have been reported to be involved in the phosphorylation of the water channel PM28A present in the spinach (Spinacia oleracea) plasma membrane (Johansson et al, 1996).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…O aumento na concentração de Ca 2+ , entretanto, não teve efeito significativo sobre a produção de matéria seca das raízes no genótipo tolerante, mas resultou em redução de cerca de 11 % no genótipo sensível (Quadro 2). Os efeitos do Ca 2+ sobre o crescimento radicular de plantas submetidas a estresse salino têm-se mostrado bastante variáveis, podendo ir desde pequenas reduções, como as observadas no presente estudo, até aumentos bastante significativos, dependendo da espécie, das condições experimentais e de outros fatores (Cramer et al, 1986). O estresse salino resultou em aumento bastante elevado nos teores de Na + e de Cl -nas folhas, principalmente no genótipo sensível (Quadro 3), o que explica, pelo menos em parte, a maior sensibilidade desse genótipo ao estresse salino (Lacerda et al, 2003).…”
Section: Resultsunclassified
“…For example, it has been shown that addition of Ca 2+ to root media containing NaCl favours plant growth in both halophytic (Colmer et al, 1996) and non-halophytic species (Cramer et al, 1986;Kinraide, 1999;LaHaye and Epstein, 1996;Suhayda et al, 1992). Calcium also reduced the toxic effects of Na + and Mg 2+ on the germination of Kalidum capsicum (Tobe et al, 2002) and Hordeum vulgare (Bliss et al, 1986).…”
Section: Discussionmentioning
confidence: 99%